Integrating the latest biological advances in the key steps of a food packaging life cycle - Rzayeva, Aynura; Coffigniez, Fanny; Zeynalov, Nizami; Gontard, Nathalie; Guillard, Valérie (Frontiers in Nutrition, 2023)
This literature review provides a focus on the potential of integrating the latest scientific and technological advances in the biological field to improve the status of the key steps of a food packaging life cycle: production, usage, post-usage, and long-term fate. A case study of such multi-biological food packaging is demonstrated based on the use of PHAs (polyhydroxyalkanoates) polymer, a microbiologically produced polymer from non-food renewable resources, activated by the use of bioactive components to enhance its usage benefits by reducing food loss and waste, displaying potential for reusability, compostability as post-usage, and finally, being ultimately biodegradable in most common natural conditions to considerably reduce the negative impact that persistent plastics have on the environment. We discuss how designing safe and efficient multi “bio” food packaging implies finding a compromise between sometimes contradictory functional properties. For example, active antimicrobials help preserve food but can hamper the ultimate biodegradation rate of the polymer. This review presents such antagonisms as well as techniques (e.g., coatings, nanoencapsulation) and tools (e.g., release kinetic) that can help design optimized, safe, and efficient active food packaging.